A qualitative examination of naloxone access in three states: Connecticut, Kentucky, and Wisconsin - Antoinette L. Spector; Carol L. Galletly; Erika A. Christenson; H. Danielle Green Montaque; Julia Dickson-Gomez (BMC, 2022)
Abstract Background Prevention of opioid-involved overdose deaths remains a public health priority in the United States. While expanding access to naloxone is a national public health strategy, it is largely implemented at the state and local level, where significant variability in policies, resources, and norms exist. The aims of the current study were to examine the social context of naloxone access in three different states (Connecticut, Kentucky, Wisconsin) from the perspectives of key informants (first responders, harm reduction personnel, and pharmacists), who play some role in dispensing or administering naloxone within their communities. Methods Interviews were conducted with key informants who were in different local areas (urban, suburban, rural) across Connecticut, Kentucky, and Wisconsin. Interview guides explored the key informants' experiences with administering or dispensing naloxone, and their perspectives on opioid overdose prevention efforts in their areas. Data analysis was conducted using multistage inductive coding and comparative methods to identify dominant themes within the data. Results Key informants in each of the three states noted progress toward expanding naloxone access, especially among people who use opioids, but also described inequities. The key role of harm reduction programs in distributing naloxone within their communities was also highlighted by participants, as well as barriers to increasing naloxone access through pharmacies. Although there was general consensus regarding the effectiveness of expanding naloxone access to prevent overdose deaths, the results indicate that communities are still grappling with stigma associated with drug use and a harm reduction approach. Conclusion Findings suggest that public health interventions that target naloxone distribution through harm reduction programs can enhance access within local communities. Strategies that address stigmatizing attitudes toward people who use drugs and harm reduction may also facilitate naloxone expansion efforts, overall, as well as policies that improve the affordability and awareness of naloxone through the pharmacy.